2017
DOI: 10.1002/er.3723
|View full text |Cite
|
Sign up to set email alerts
|

Design of robust battery capacity model for electric vehicle by incorporation of uncertainties

Abstract: Summary The improvement in the operating range of electric vehicles can be accomplished by robust modelling of the design and optimization of the energy storage capacity of the battery pack system. In this work, the authors have conducted a comprehensive survey on battery modelling methods and identified critical areas of improvement vital for estimating the battery capacity. This work proposes the artificial intelligence approach of automated neural networks search (ANS) in development of the robust battery c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Further studies are needed to consider analysis of data using copula modelling approaches (Panda et al, 2017(Panda et al, , 2018Zhang et al, 2017aZhang et al, , 2017bGarg et al, 2017b;Garg et al, 2017c). Further, it was found that soil temperature is the most significant parameter influencing electrical conductivity for bare soil whereas, soil water content is important for tree-covered soil.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to consider analysis of data using copula modelling approaches (Panda et al, 2017(Panda et al, , 2018Zhang et al, 2017aZhang et al, , 2017bGarg et al, 2017b;Garg et al, 2017c). Further, it was found that soil temperature is the most significant parameter influencing electrical conductivity for bare soil whereas, soil water content is important for tree-covered soil.…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity in the calculation of the air-gap field, the effect of slotting is ignored. The air-gap field produced by PMs in the slotless air gap is given by Equations (3) and (4) ( )…”
Section: Cogging Torquementioning
confidence: 99%
“…In the transportation sector, some new technologies, such as cleaner energy storage systems [3,4], high-efficiency electric drive systems [5], electric vehicles (EVs), and hybrid EVs (HEVs) have been extensively researched with the aim of reducing exhaust emissions [6,7]. As motors represent a key form of technology for EVs and HEVs, their design is fundamental.…”
Section: Introductionmentioning
confidence: 99%
“…The battery pack's electrochemical behavior is not identical to that of the single cell, due to cell variation . The influence of the cell variations on the management of battery pack should be clarified to guarantee safe and efficient operations . However, there is still some knowledge gap between the pack behavior and the cell behavior hindering the application of batteries, thereby arousing active researches in this area.…”
Section: Introductionmentioning
confidence: 99%